Total Synthesis of Surinamensinols A and B - Avula, Satya Kumar; Das, Biswanath; Csuk, Rene; Al-Rawahi, Ahmed; Al-Harrasi, Ahmed (SynOpen, 2020)
An efficient total synthesis of the naturally occurring anti-inflammatory and antitumour 8-O-4′-neolignans, surinamensinols A and B, has been accomplished from commercially available allyl alcohol and (S)-ethyl lactate. The synthetic sequence involves a palladium-catalysed Suzuki–Miyaura cross-coupling reaction followed by a chiral Mitsunobu reaction as the key steps. This is the first report of the simultaneous stereoselective total synthesis of surinamensinols A and B through a single approach involving only six steps.
Keywords: Surinamensinol A B; anti-inflammatory and antitumour neolignans; stereoselective total synthesis; Suzuki–Miyaura cross coupling; Mitsunobu reaction